The importance of carbonic anhydrase II in red blood cells during exposure of chicken embryos to CO2. - Everaert, N; Willemsen, H; Hulikova, A; Brown, H; Decuypere, E; Swietach, P; Bruggeman, V (2010)
The importance of carbonic anhydrase (CA) during exposure of chicken embryos to CO(2) during the second half of incubation was investigated. The protein abundance and activity of CAII in erythrocytes was significantly higher in CO(2)-exposed embryos compared to normal conditions. Daily injections of acetazolamide (ATZ), an inhibitor of CA, increased blood P(CO2) and decreased blood pH in both control and CO(2)-incubated embryos. ATZ increased blood bicarbonate concentration in embryos exposed to normal atmosphere and in day-12 embryos exposed to high CO(2). The tendency of an increased blood potassium concentration in ATZ-injected embryos under standard atmospheric conditions might indicate that protons were exchanged with intracellular potassium. However, there was no evidence for such an exchange in CO(2)-incubated ATZ-treated embryos. This study shows for the first time that chicken embryos adapt to CO(2) during the second half of incubation by increasing CAII protein expression and function in red blood cells. This response may serve to "buffer" elevated CO(2) levels.